2020
DOI: 10.1186/s12885-020-07257-7
|View full text |Cite
|
Sign up to set email alerts
|

Tissue mechanics and expression of TROP2 in oral squamous cell carcinoma with varying differentiation

Abstract: Background: Trophoblast cell surface antigen 2 (TROP2) is overexpressed in many squamous cell carcinomas and promotes tumor development and invasion. The association between TROP2 expression and occurrence and development of oral squamous cell carcinoma (OSCC) remains to be understood. Methods: We investigated the role of TROP2 in OSCC patients using a combination of biophysical approaches. A total of 108 OSCC patient specimens with varying degrees of differentiation were subjected to hematoxylin and eosin sta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 42 publications
(45 reference statements)
3
10
3
Order By: Relevance
“…To analyze the cytoplasmic expression, they used another primary antibody against Trop-2. Moreover, they did not compare central vs. peripheral expression [ 16 ]. Hence, their results are not directly comparable with ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the cytoplasmic expression, they used another primary antibody against Trop-2. Moreover, they did not compare central vs. peripheral expression [ 16 ]. Hence, their results are not directly comparable with ours.…”
Section: Discussionmentioning
confidence: 99%
“…In several cancer entities, Trop-2 protein expression may be used as an independent prognostic marker (summarized in [ 15 ]). In OSCC, high Trop-2 protein expression was reported to be associated with tumor grade and poor overall survival [ 16 , 17 ]. One reason may be the role of Trop-2 as an activator of the phosphoinositide 3-kinase (PI3K)/Akt signaling pathway in human OSCC cells [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Zhang et al 25 reported a significant correlation of TROP2 with poorly differentiated oral SCC. Furthermore, TROP2 has been actively studied as a prognostic marker for various cancers including colon cancer and oral SCC.…”
Section: Discussionmentioning
confidence: 97%
“… 21 Although it is down-regulated in cholangiocarcinoma, 21 TROP2 was highly expressed in various human cancers as lung, 22 cervix 23 and oral SCC. 24 , 25 Regarding BCC and cutaneous SCC, the role of TROP2 was not yet identified.…”
Section: Introductionmentioning
confidence: 99%
“…1 ) to hard ( Fig. 2 ) PAAs to mimic normal tissue and tumor-associated mechanical properties, respectively, in vitro [6] , [7] , [8] . Physical contact and interactions between HNSCC cells in pairs on the soft ( Fig.…”
Section: Data Descriptionmentioning
confidence: 99%